2001
DOI: 10.1074/jbc.m101678200
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeletal/Non-muscle Isoform of α-Actinin Is Phosphorylated on Its Actin-binding Domain by the Focal Adhesion Kinase

Abstract: ␣-Actinin is tyrosine-phosphorylated in activated human platelets (Izaguirre, G., Aguirre, L., Ji, P., Aneskievich, B., and Haimovich, B. (1999) J. Biol. Chem. 274, 37012-37020). Analysis of platelet RNA by reverse transcription-polymerase chain reaction revealed that ␣-actinin expressed in platelets is identical to the cytoskeletal/non-muscle isoform. A construct of this isoform containing a His 6 tag at the amino terminus was generated. Robust tyrosine phosphorylation of the recombinant protein was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(162 citation statements)
references
References 65 publications
4
155
1
2
Order By: Relevance
“…For example, ␣-actinin was detected in IMAC eluates and Tyr(P) IPs only after pV stimulation in agreement with published work (38,39) that indicates that this protein is reversibly phosphorylated. Tyr-12 phosphorylation of ␣-actinin, previously detected upon pV treatment (39), was not identified in our analyses.…”
Section: Identification Of Proteins Phosphorylated At Tyr Residues (Asupporting
confidence: 91%
“…For example, ␣-actinin was detected in IMAC eluates and Tyr(P) IPs only after pV stimulation in agreement with published work (38,39) that indicates that this protein is reversibly phosphorylated. Tyr-12 phosphorylation of ␣-actinin, previously detected upon pV treatment (39), was not identified in our analyses.…”
Section: Identification Of Proteins Phosphorylated At Tyr Residues (Asupporting
confidence: 91%
“…Because of its localization in focal adhesions, ␣-actinin was suggested to anchor the actin filaments to the plasma membrane (52). Recently, FAK was found to phosphorylate ␣-actinin, thereby reducing the interactions between ␣-actinin and actin filaments (53). A decrease in the affinity of ␣-actinin for actin resulting from phosphorylation by FAK could facilitate the turnover of focal adhesions as a result of diminished contact with the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] FAK may also decrease integrin-cytoskeleton linkages through α-actinin phosphorylation, which reduces its affinity for actin. 41,42 Biochemical experiments performed in COS and PTP1B-null cells suggested that PTP1B could dephosphorylate α-actinin and promote chemotaxis to fibronectin. 43 We postulated that PTP1B dephosphorylates α-actinin in adhesions facilitating its binding to actin (Fig.…”
Section: Ptp1b Regulation Of Cell-matrix Coupling To the Cytoskeletonmentioning
confidence: 99%